Estimasi Rata-Rata Konsumsi Kopi Mahasiswa Universitas Pamulang Menggunakan Metode Point Estimate dan Confidence Interval - Gilang Pratama; Maharani Putri Junaidi; Bagua Pribadi; Diky Eka Purnomo (CV. Multi Kreasi Media, 2025)
This study aims to estimate the average coffee consumption of Pamulang University students using the point estimate and confidence interval methods. The research employed a descriptive quantitative approach using primary data collected through an online questionnaire distributed to active students of the Informatics Engineering Study Program. The analyzed variable was weekly coffee consumption measured in cups. Data analysis was conducted using descriptive statistics to obtain the mean, median, mode, and standard deviation. The point estimate method was applied to obtain a single estimated value of average coffee consumption, while the confidence interval method was used to determine the population mean range with a 95% confidence level. The results indicate that the average coffee consumption of Pamulang University students is 4.5 cups per week. The 95% confidence interval shows that the population mean lies between 3.60 and 5.40 cups per week. These findings provide an objective statistical description of students’ coffee consumption patterns and may serve as a reference for further research related to student lifestyle and health.